Dal'nii Vostok . Dal'nii Vostok . The Far East . Дальний Восток - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Meeting of the small regional council of the Sakhalin region; conflict with Korea over fishing in the Okhotsk Sea; traffic checks in Vladivostok; ecological problems. Russian-American theater festival. Contributors: Voropaev, Vladimir (Anchor) Series description: The program consists of regional television reports of the Dal'nevostochnogo federal'nogo okrug [Far Eastern Federal District] of the Russian Federation. Заседание малого областного совета Сахалинской области; конфликт с Кореей по поводу рыбной ловли в Охотском море; инспекция дорожного движения во Владивостоке; экологические проблемы. Российско-Американский театральный фестиваль. Создатели: Воропаев, Владимир (Ведущий/Ведущая) Описание серии: Программа состоит из репортажей регионального телевидения Дальневосточного федерального округа Росчсийской Федерации.